Approximations to the Tibial Distal Anatomical Axis in the Sagittal Plane - Miles, James E. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to compare approximations to the tibial distal anatomical axis (DAA) with regression lines for the symmetric axis of the tibia, and to identify an optimal approximation for surgical planning of osteotomies for the management of canine cruciate ligament deficiency.Study Design Prospective radiographic study of 20 canine tibiae. Using curve-fitting and the symmetric axis technique, the true anatomical axis was identified for each tibia. Regression lines were calculated for the distal 67% and distal 50% subsections of this axis. Angular deviations between these lines and DAA approximations were calculated and compared with to find the closest approximations.Results The DAA approximations based on the distal 50% rather than the distal 67% of the tibia had smaller maximal deviations from the true axis. Landmarks at 50% and 75% of tibial length exhibited greater deviations than those at 50% and 95% or 100%.Conclusion The DAA landmarks should be restricted to the distal half of the tibia. Use of a distal landmark either just proximal to the distal metaphyseal flare of the tibia or at the mid-point of the distal articular surface is to be preferred. In this way, the DAA will better reflect the true anatomical axis of the distal tibia.
Keywords: radiography; osteotomy; surgical planning; tibia; distal anatomical axis